Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
9514 1404 393
Answer:
x = -20
Step-by-step explanation:
First, simplify the equation. Eliminate parentheses and combine terms.
3(x -1) -8 = 4(1 +x) +5 . . . . . . . given
3x -3 -8 = 4 +4x +5 . . . . . . . . eliminate parentheses (distributive property)
3x -11 = 4x +9 . . . . . . . . . . . . combine like terms
We can put all the x-terms on the right by subtracting 3x from both sides.
3x -11 -3x = 4x +9 -3x
-11 = x +9
And we can get the x-term by itself by subtracting 9 from both sides.
-11 -9 = x +9 -9
-20 = x . . . . . . . . . . this is the solution
__
Check
3(-20 -1) -8 = 4(1 -20) +5
3(-21) -8 = 4(-19) +5
-63 -8 = -76 +5
-71 = -71 . . . . . . . . . true, the answer checks OK
_____
Additional comment
We observe that the two x-terms are 3x and 4x. The smaller of these is 3x, so when we subtract that from 4x we will have a positive result. That is why we chose to subtract 3x, even though it leaves the x-term on the right side of the equation. We could have subtracted 4x to get -x -11 = 9. I find it easier not to make a mistake if the variable has a positive coefficient.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.